Implementasi Project Based Learning (PJBL) Dalam Kerangka Kurikulum Merdeka Pada Pembelajaran Sosiologi - Septiandini, Devi; Suyuti, Suyuti; Arriany, Ike; Martina, Tina (Peneliti.net, 2024)
This research aims to describe the implementation of Project Based Learning (PjBL) in sociology learning within the framework of the independent curriculum. This research uses a qualitative approach. Data collection was obtained through observations of the learning process, interviews and literature study. This research was conducted at SMAN 62 Jakarta with research subjects namely 30 students and one teacher in class determining learning objectives, 2) theme selection, 3) group formation, 4) data and information search, 5) project planning, 6) gallery development, 7) creation of presentation materials, 8) Project Implementation, 9) Gallery Exhibition, 10) Evaluation, 11) Reflection and 12) Feedback. The results of this research show that students are more active in seeking knowledge from various sources, building collaboration with other students through group learning, increasing critical thinking skills through questions asked during discussions and improving communication skills through presentations of project results